Management of critical controls in the reduction of work accidents in the Yumpag Project - Ortega Hilario, Jhon Albertho (2023)
The Yumpag Project faces a particular reality regarding the management of critical controls in the reduction of work accidents, this situation is reflected in an increase in occupational accidents, danger to the safety of workers, as well as the productivity of operations. He maintained as an objective to determine the degree of influence of the management of critical controls towards the reduction of work accidents. It was a quantitative, explanatory, basic study, with a non-experimental design. A sample amount of 70 collaborators was used, using the questionnaires. The results revealed that the current situation of critical control management was deficient (55.7%) while the level of reduction in work accidents was low (57.1%). In addition, the degree of influence was 54.5%, 52.4% and 48.4% of the management of critical controls towards the dimensions of work accidents were significant and positive. Consequently, it is concluded that there is a significant and positive influence represented in 52.7% between the management of critical controls towards the reduction of work accidents in said mining project.